Characteristics of Clinical and Magnetic Resonance, and Treatment Result for Anterior Cruciate Ligament Tear of the Knee Joint - Ngoc, Pham Thi Minh; Son, Nguyen Van (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 38 No 2DO - 10.25073/2588-1132/vnumps.4407, 2022)
Study on 41 patients with anterior cruciate ligament rupture diagnosed and treated at E Hospital from March 2021 to April 2022 showed: Mean age: 36.02, Male: 68.3%, female: 27.7%. Traffic accidents: 65.9%. Right foot: 53.7%, left foot: 44.3%. Timefrom injury to treatment > 3 weeks: 70.7%. Clinical: loose knee: 90.2%; pain: 87.8%; difficulty going up and down stairs: 65.9%; knee swelling: 51.2%; effusion: 68.3%; front drawer: 95.1%; Lachman: 92.7%; McMurray: 41.4%; average Lysholm score: 60.88. Magnetic resonance imaging (MRI): decompression/intermittent: complete: 52.7%, partial: 46.3%; contusion, edema: 41.5%; hematoma-hemorrhage: 87.7%; bone marrow edema: 34.1%; meniscus tear: 46.3%. Treatment results: pain relief upon discharge: 70.7%; incision: dry: 56.1% drainage: 43.9%, infection: 0, after follow-up: mean Lysholm score: 86.95, complications: numbness, burning behind the thigh: 2.44%.